2009
DOI: 10.2174/187152509789105471
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus (RSV) Prevention and Treatment: Past, Present, and Future

Abstract: Respiratory syncytial virus (RSV) is a very important pathogen worldwide. It occurs and recurs naturally throughout life. Both short and long term morbidity, and mortality are particularly significant for infants, especially those infants with underlying conditions and risk factors. Current treatment strategies for these patients (e.g Ribavirin) are limited but several new interventions (e.g. RSV604, BTA9881, ALN-RSV01) are under investigation. Several preventive agents and strategies have been developed (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Briefly, 100 g/ml of SB105-A10 (21.3 M) was applied to the apical surface at the air-tissue interface for 0.5, 1, 4, and 18 h at 37°C, and tissues were then analyzed for (i) the reduction of tetrazolium salt (MTT), to study the metabolic activity of the living cells; (ii) lactate dehydrogenase (LDH) release, to measure the accumulation of dead cells; and (iii) the release of IL-8, to evaluate inflammatory activation of cells (see Materials and Methods for further details). As reported in Table 2, SB105-A10 was not cytotoxic, and the time required to reduce tissue viability to 50% (ET 50 ) was greater than 18 h. No significant difference in the release of the cytoplasmic enzyme LDH was observed between SB105-A10-treated and untreated tissues. Finally, our results indicate that human-derived tracheal and bronchial epithelial cells exposed to SB105-A10 do not exhibit significant differences in levels of the proinflammatory cytokine IL-8 (Table 2) compared to untreated samples.…”
Section: Effect Of Sb105-a10 On Viral Infectivitymentioning
confidence: 71%
See 1 more Smart Citation
“…Briefly, 100 g/ml of SB105-A10 (21.3 M) was applied to the apical surface at the air-tissue interface for 0.5, 1, 4, and 18 h at 37°C, and tissues were then analyzed for (i) the reduction of tetrazolium salt (MTT), to study the metabolic activity of the living cells; (ii) lactate dehydrogenase (LDH) release, to measure the accumulation of dead cells; and (iii) the release of IL-8, to evaluate inflammatory activation of cells (see Materials and Methods for further details). As reported in Table 2, SB105-A10 was not cytotoxic, and the time required to reduce tissue viability to 50% (ET 50 ) was greater than 18 h. No significant difference in the release of the cytoplasmic enzyme LDH was observed between SB105-A10-treated and untreated tissues. Finally, our results indicate that human-derived tracheal and bronchial epithelial cells exposed to SB105-A10 do not exhibit significant differences in levels of the proinflammatory cytokine IL-8 (Table 2) compared to untreated samples.…”
Section: Effect Of Sb105-a10 On Viral Infectivitymentioning
confidence: 71%
“…The hospitalization of RSV patients in the United States produces an annual economic burden of approximately $500 million, and considerable further costs can be added to this figure as a result of outpatient care (18,35). The management of RSV infection is primarily a matter of treating symptoms (8), and antiviral treatment is limited to the use of ribavirin, a drug which has controversial activity and is associated with significant side effects (11,45,50). Palivizumab, a humanized monoclonal antibody, has been approved for the immunoprophylaxis of RSV infection in just one narrowly defined patient group: high-risk prematurely born infants (23,55).…”
mentioning
confidence: 99%
“…MEDI-557 (motavizumab-YTE) is a third generation, humanized mAb derived from motavizumab, in which three amino acid substitutions (M252Y/S254T/T256E [YTE]) were introduced in the IgG 1 Fc region, extending the serum IgG half-life [53]. A Phase-I randomized double blind, dose escalation study to evaluate the safety, tolerability and pharmacokinetics of this mAb showed that the clearance of motavizumab-YTE was significantly lower and the half-life up to 4-fold longer than motavizumab [54].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…MEDI-557 is a third-generation humanized monoclonal antibody developed from motavizumab by introducing amino acid substitutions in the IgG1 Fc fragment [77]. Both palivizumab and motavizumab have a half-life of about 3 weeks, and need to be given via monthly intramuscular injections throughout the RSV season.…”
Section: Medi-557mentioning
confidence: 99%